2023
DOI: 10.2106/jbjs.oa.23.00049
|View full text |Cite
|
Sign up to set email alerts
|

Match Rates Among Underrepresented Minority and Female Applicants to Orthopaedic Surgery Residency Programs from 2011 to 2021

Andrew B. Harris,
Ashish Vankara,
Claire McDaniel
et al.

Abstract: Background: Orthopaedic surgery residency programs have traditionally had less representation of underrepresented minority (URM) and female trainees compared with other medical specialties. Widespread efforts have been implemented to increase the diversity of orthopaedic surgery residency programs; however, it is not known whether URM and female applicants are increasingly likely to match as a result. Thus, we aimed to study the independent association between URM and female applicants and matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They found that URiM applicants were not markedly more likely to match than non-URiM applicants. Examining trends from 2011 to 2021 in orthopaedic applicants, Harris et al 18 demonstrated that URiM women (from 0.46 [95% CI, 0.40 to 0.52] to 0.61 [95% CI, 0.56 to 0.65]) were the only demographic group with a markedly increased odds ratio of matching over that period. Nevertheless, even in 2021, this OR was less than that of the general application pool (OR, 0.72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that URiM applicants were not markedly more likely to match than non-URiM applicants. Examining trends from 2011 to 2021 in orthopaedic applicants, Harris et al 18 demonstrated that URiM women (from 0.46 [95% CI, 0.40 to 0.52] to 0.61 [95% CI, 0.56 to 0.65]) were the only demographic group with a markedly increased odds ratio of matching over that period. Nevertheless, even in 2021, this OR was less than that of the general application pool (OR, 0.72).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even in 2021, this OR was less than that of the general application pool (OR, 0.72). 18…”
Section: Discussionmentioning
confidence: 99%